2019
DOI: 10.1111/hiv.12758
|View full text |Cite
|
Sign up to set email alerts
|

Towards person‐centred care for people living with HIV: what core outcomes matter, and how might we assess them? A cross‐national multi‐centre qualitative study with key stakeholders

Abstract: Objectives People living with HIV (PLWH) have multidimensional concerns requiring person‐centred care. Routine use of patient‐reported outcome measures (PROMs) improves outcomes. No brief PROM currently reflects the breadth of concerns for PLWH. This study sought to identify priority outcomes for PLWH, model current practice, explore views on introducing PROMs into routine care, and devise a model for person‐centred care incorporating the PROM. Methods A cross‐national multi‐centre study (London, Brighton and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 26 publications
(34 reference statements)
1
77
0
Order By: Relevance
“…Polypharmacy rates among PLHIV, which range from 23% to 39%, are higher than among HIV-negative populations (11)(12)(13)(14)(15). Studies have demonstrated associations between polypharmacy and clinical outcomes, including death (16); however, data are scarce on the relationship between polypharmacy and overall quality of life based on subjective measures of well-being that are important to patients (17,18), including their experiences, concerns, and treatment priorities. To fill these gaps in knowledge, we used pooled data from 24 countries to examine associations between polypharmacy and self-rated overall health and perceptions of treatment needs.…”
Section: Introductionmentioning
confidence: 99%
“…Polypharmacy rates among PLHIV, which range from 23% to 39%, are higher than among HIV-negative populations (11)(12)(13)(14)(15). Studies have demonstrated associations between polypharmacy and clinical outcomes, including death (16); however, data are scarce on the relationship between polypharmacy and overall quality of life based on subjective measures of well-being that are important to patients (17,18), including their experiences, concerns, and treatment priorities. To fill these gaps in knowledge, we used pooled data from 24 countries to examine associations between polypharmacy and self-rated overall health and perceptions of treatment needs.…”
Section: Introductionmentioning
confidence: 99%
“…with HIV to articulate their health challenges and needs, facilitate goal-setting, and guide referrals to available services. At the service delivery level, the SF-HDQ may help clinics or community-based organizations to better understand the changing needs of individuals as they age with HIV, evaluate the impact of interventions, programs and models of service delivery, and inform areas of resource allocation for future programming and service provision [68].…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…Despite advances in antiretroviral therapy (ART), people living with HIV have worse health related quality of life than the general population [2], and disproportionate burden of poor mental health [3,4]. Their physical, cognitive, psychological, social, spiritual, welfare and informational needs are highly interrelated, and persisting HIV stigma can reduce access to appropriate support [5]. A holistic approach to HIV treatment and care is needed, focused on the individual, rather than treating symptoms and concerns in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Global HIV policy and public health initiatives continue to focus attention on diagnosis, treatment adherence and viral suppression in order to end the HIV/ AIDS epidemic [6]. People living with HIV have long reported that this focus on viral suppression and treatment adherence is reflected within clinical consultations, with a lack of attention or opportunity to discuss needs beyond ART-related concerns [5,7,8]. Care that focuses on what matters to the individual, and is respectful and responsive to their needs, can improve care experiences and health outcomes [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation